2015
DOI: 10.1002/sm2.76
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Testosterone Gels, Injections, and Pellets on Serum Hormones, Erythrocytosis, Lipids, and Prostate-Specific Antigen

Abstract: IntroductionNumerous testosterone (T) formulations are available, each with differing effects on serum parameters.AimThe aim of this study was to compare the long-term effects of topical, injectable, and implantable pellet T formulations in hypogonadal men.MethodsRetrospective review of hypogonadal men treated with a single T formulation was performed: 47 men on T gels, 57 on injectable T, and 74 on T pellets were identified. Total T (TT), calculated free T (FT), estradiol (E), hemoglobin (Hgb), hematocrit (Hc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
57
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 53 publications
3
57
0
1
Order By: Relevance
“…Male hypogonadism is defined as the presence of both low serum testosterone levels as well as symptoms that can include decreased libido, erectile dysfunction, loss of vitality, loss of lean muscle and bone density, fatigue, anemia and depression (1). The prevalence of hypogonadism has proven difficult to accurately determine, with the highest reported prevalence reported in 2006 when Mulligan et al found that 40% of men over age 45 had symptomatic hypogonadism (2).…”
Section: Introductionmentioning
confidence: 99%
“…Male hypogonadism is defined as the presence of both low serum testosterone levels as well as symptoms that can include decreased libido, erectile dysfunction, loss of vitality, loss of lean muscle and bone density, fatigue, anemia and depression (1). The prevalence of hypogonadism has proven difficult to accurately determine, with the highest reported prevalence reported in 2006 when Mulligan et al found that 40% of men over age 45 had symptomatic hypogonadism (2).…”
Section: Introductionmentioning
confidence: 99%
“…Testosterone replacement therapy (TRT) is the first‐line treatment for testosterone deficiency and has been shown to improve bone density, alleviate depression, and maintain sexual function 5. Currently available options for TRT in the United States include intramuscular injections, transdermal patches, and gels 6, 7. The development of an oral TRT has been extremely challenging because of extensive first pass metabolism.…”
mentioning
confidence: 99%
“…The development of an oral TRT has been extremely challenging because of extensive first pass metabolism. As a result, the 2–4 million hypogonadal men in the United States requiring TRT mainly rely on intramuscular or topical testosterone dosage forms,6, 7 both of which are challenging in terms of compliance, and have suboptimal pharmacokinetics (PK) or variable absorption 8. Clearly, the development of a safe and effective formulation of oral testosterone is a major unmet need for these men.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[21] Treatment with exogenous testosterone is associated with several adverse sequelae, the most common of which are erythrocytosis, elevated serum estrogen levels, alterations in serum lipids, and infertility. [2] An increased cardiovascular risk in men using exogenous testosterone has also been proposed, although high quality evidence examining this relationship remains lacking.…”
Section: Introductionmentioning
confidence: 99%